2022
DOI: 10.3390/su142316108
|View full text |Cite
|
Sign up to set email alerts
|

Telework Implications on Work-Life Balance, Productivity, and Health of Different Generations of Romanian Employees

Abstract: The purpose of this article is to analyse the impact of telework on the work-life balance, productivity, and health of different generations of Romanian employees. Qualitative and quantitative methods provide the means to exploit the richness of data and deepen the understanding of the phenomenon studied. The quantitative data derived from a research instrument was associated with qualitative data collection. Quantitative research was conducted to achieve the stated purpose using the survey method, the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
(87 reference statements)
1
10
0
1
Order By: Relevance
“…The existence of some positive influences between working from home and the feeling of professional isolation felt daily by fully remote employees (β = 0.423; T-value = 3.184; p < 0.01) was demonstrated, but also for those working partially from home (β = 0.283; T-value = 2.364; p < 0.05) [38]. During the COVID-19 pandemic, organisations that adopted teleworking provided a large variety of technological tools for maintaining good communication, but this was not enough to avoid professional isolation [50], social isolation, marginalisation, and other forms of deterioration in the quality of relationships between co-workers and employees [124]. Therefore, professional isolation becomes a negative outcome of telework (see H4).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The existence of some positive influences between working from home and the feeling of professional isolation felt daily by fully remote employees (β = 0.423; T-value = 3.184; p < 0.01) was demonstrated, but also for those working partially from home (β = 0.283; T-value = 2.364; p < 0.05) [38]. During the COVID-19 pandemic, organisations that adopted teleworking provided a large variety of technological tools for maintaining good communication, but this was not enough to avoid professional isolation [50], social isolation, marginalisation, and other forms of deterioration in the quality of relationships between co-workers and employees [124]. Therefore, professional isolation becomes a negative outcome of telework (see H4).…”
Section: Discussionmentioning
confidence: 98%
“…One study concluded that teleworking generated strain for employees in the form of work-family conflicts due to difficulty of detaching themselves from work at the end of the day. Personal difficulties and remote working contributed to the feeling of professional disconnection between teleworkers and their co-workers and their supervisors [50]. Another study found that work-life conflict was generated because many employees were required to work with children, teenagers, or young adults who were also working from home, generating a difficult management of boundaries which increased conflict [103].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of nomophobia and FoMO is increasing for employees (Farivar & Richardson, 2021;Marsh et al, 2022) due to reasons such as the use of mobile technologies to perform more tasks at work for millennials and becoming a part of organizational environments, providing temporal and spatial flexibilities on the one hand, and the potential to interrupt other activities such as e-mail, notifications, etc. outside of working hours (Ivasciuc et al, 2022). Studies addressing these risks have mainly focused on the effects of nomophobia or FoMO.…”
Section: Literaturementioning
confidence: 99%